The Effect of Public Service and Financial Compensation and Professionalism on Employee Performance With Job Satisfaction As An Intervening Variable At Muara Wahau District Office - Susanti, Emilia; Yudhyani, Eka; Iskandar, Rusdiah (LPPM of NAROTAMA UNIVERSITY, 2025)
Purpose: The Influence of Public Service and Financial Compensation and Professionalism on Employee Performance with Job Satisfaction as an Intervening Variable.Design/methodology/approach: The research method uses quantitative research with analysis tools using path analysis, with 27 respondents, this research sample was obtained using the saturated sampling technique because the population is limited. Data collection carried out was field research (surveys and questionnaires) and literature.Findings: Service motivation has no significant effect on employee job satisfaction Financial compensation has a significant effect on job satisfaction, professionalism has a significant effect on job satisfaction, Job satisfaction has a significant effect on employee performance, Service motivation has no significant effect on employee performance, Financial compensation has a significant effect on employee performance, Professionalism has a significant effect on employee performance, Public service motivation has no significant effect on employee performance through job satisfaction, Financial compensation has a significant effect on employee performance through job satisfaction, Professionalism has a significant effect on employee performance through job satisfactionResearch limitations/implications: Time of researchOriginality/value: The originality of this study is based on several previous studies that have relatively similar characteristics in terms of research themes, although different in terms of subject criteria, number, and position of research variables or analysis methods used